Natural terpenoids with therapeutic potential against pulmonary arterial hypertension - Dang, Kaijie; Zhang, Junru; Yu, Kexin; Liu, Xinyu; Zhu, Yi; Yang, Xiuli; Liu, Xiao; Zhang, Chuantao (Frontiers in Pharmacology, 2026)
Pulmonary arterial hypertension (PAH) is a devastating disorder characterized by progressive pulmonary vascular remodeling, chronic inflammation, and right heart failure. Current vasodilation-focused therapeutic strategies often fail to reverse established vascular structural lesions and inadequately control disease progression. Natural terpenoids demonstrate significant anti-remodeling potential through their structural diversity and multi-target intervention capabilities, including suppression of oxidative stress, blockade of inflammatory pathways, regulation of endothelial-mesenchymal transition (EndMT), restoration of the cellular proliferation/apoptosis balance, and recovery of ion channel functionality. This review systematically summarizes the pharmacological effects, molecular mechanisms, and limitations of natural terpenoids in ameliorating PAH, providing novel perspectives for targeted therapies. To advance clinical translation, future efforts must prioritize large-scale trials validating safety profiles and optimizing dosing regimens, while diversifying natural sources to accelerate precision drug development.